2008
DOI: 10.1111/j.1755-5949.2008.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol: A Natural Compound with Pharmacological Potential in Neurodegenerative Diseases

Abstract: Resveratrol is a phytoalexin structurally related to stilbenes, which is synthesized in considerable amounts in the skin of grapes, raspberries, mulberries, pistachios and peanuts, and by at least 72 medicinal and edible plant species in response to stress conditions. It was isolated in 1940 and did not maintain much interest for around five decades until its role in treatment of cardiovascular diseases was suggested. To date, resveratrol has been identified as an agent that may be useful to treat cancer, pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
88
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(95 citation statements)
references
References 126 publications
(182 reference statements)
1
88
1
5
Order By: Relevance
“…In return, Aβ can inhibit the activity of alcohol dehydrogenase [52], suggesting that inactivity of ADH3 leads to formaldehyde accumulation. In addition, a natural formaldehyde capturer [56], resveratrol, provides effective defence against cancer and neurodegenerative disease including AD [57,58]. Recent research has also shown that dietary supplementation with resveratrol reduces senile plaque (SP) pathology in a APP/PS1-transgenic model of AD [55].…”
Section: Excess Formaldehyde Promotes the Occurrence Of Both Genetic mentioning
confidence: 99%
“…In return, Aβ can inhibit the activity of alcohol dehydrogenase [52], suggesting that inactivity of ADH3 leads to formaldehyde accumulation. In addition, a natural formaldehyde capturer [56], resveratrol, provides effective defence against cancer and neurodegenerative disease including AD [57,58]. Recent research has also shown that dietary supplementation with resveratrol reduces senile plaque (SP) pathology in a APP/PS1-transgenic model of AD [55].…”
Section: Excess Formaldehyde Promotes the Occurrence Of Both Genetic mentioning
confidence: 99%
“…40c, [71][72][73] Na última década, além dos aspectos comportamentais típicos da instalação da DA, surgiram fortes evidências da ocorrência de um complexo processo inflamatório no tecido neuronal. A relevância da neuroinflamação na instalação, progressão e na severidade da DA, assim como dos mecanismos de ativação do sistema imune e de células-chave ao disparo da cascata inflamatória no SNC, como a microglia e astrócitos, têm sido demonstrada na literatura em importantes trabalhos de revisão.…”
unclassified
“…A relevância da neuroinflamação na instalação, progressão e na severidade da DA, assim como dos mecanismos de ativação do sistema imune e de células-chave ao disparo da cascata inflamatória no SNC, como a microglia e astrócitos, têm sido demonstrada na literatura em importantes trabalhos de revisão. 74,[71][72][73] Apesar dos resultados experimentais não serem conclusivos, parece que a deposição anormal de f ag e tosà i solúveisà deà βáà ãoà à espo s velà po à todo o espectro de sintomas clínicos da doença, principalmente aqueles observados antes da neurodegeneração tornar-se evidente. Alterações inflamatórias são observadas no cérebro, principalmente nas regiões com depósito amiloide, que são ricas em células microgliais ativadas.…”
unclassified
See 1 more Smart Citation
“…This concept refers to the observation that in certain regions of France, lower than expected mortality from coronary heart disease was found (despite high intake of saturated fat), which was correlated to high red wine consumption (24). Moreover, interest in red wine polyphenols as therapeutic agents-in particular resveratrol, due to its strong antioxidant, anti-inflammatory, anti-ischemic and chemopreventive properties-has been growing, with several health benefits described in cancer and cardiovascular prevention, and protection against neurodegenerative disorders such as Alzheimer's, Parkinson's and Huntington's diseases (25,26). More specifically in AD, in vivo administration of resveratrol resulted in reduced neurodegeneration and cognitive decline in mice displaying AD features (27,28), while in vitro resveratrol lowered the levels of secreted and intracellular Aβ peptides produced from different cell lines by promoting Aβ degradation (29).…”
mentioning
confidence: 99%